Corporate Criminal Liability Against Pollution Environment Life - T. Riza Zarzani; Ismaidar Ismaidar; Muhammad Mujahidin Za (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Environmental pollution that exceeds quality standards is often carried out by corporations. Law enforcement in the environmental sector, in addition to resolution through administrative law, also through the application of criminal law. In recent developments, law enforcement in the environmental sector has moved closer to a premium remedy . This research aims to analyze feasibility effective application of law in the environmental sector through normative legal research or library legal research using a juridical approach. In this research, it can be concluded that by implementing administrative sanctions against corporations, we should also apply criminal law to corporations that have repeatedly polluted the environment, so that the aim of the law, namely justice, can be accepted by the living creatures affected by it.